PCBP-1 Regulates the Transcription and Alternative Splicing of Inflammation and Ubiquitination-Related Genes in PC12 Cell - Yusufujiang, Aishanjiang; Zeng, Shan; Yang, Chen; Jing, Sha; Yang, Lijuan; Li, Hongyan (Frontiers in Aging Neuroscience, 2022)
PCBP-1, a multifunctional RNA binding protein, is expressed in various human cell/tissue types and involved in post-transcriptional gene regulation. PCBP-1 has important roles in cellular Iron homeostasis, mitochondrial stability, and other cellular activities involved in the pathophysiological process of neurodegenerative diseases, such as amyotrophic lateral sclerosis (ALS) and Huntington’s disease (HD). However, it remains enigmatic whether PCPB-1 is associated with the pathogenesis of PD. In this study, we cloned and constitutively overexpressed PCBP-1 in rat PC12 cells (PC12 cell is the common cell line studying neurodegenerative disease include PD). RNA-seq was performed to analyze PCBP-1-regulated differentially expressed genes (DEGs) and alternative splicing events (ASEs) between control and PCBP1-overexpressed cells. GO and KEGG pathway analyses were performed to identify functional DEGs and alternatively spliced genes. Consequently, we validated PCBP-1-regulated genes using RT-qPCR. Finally, we downloaded CLIP-seq data from GEO (GSE84700) to analyze the mechanisms of PCBP-1’s regulation of gene expression and ASEs by revealing the binding profile of PCBP-1 on its target pre-mRNAs. Overexpression of PCBP-1 partially regulated the ASE and expression of genes enriched in neuroinflammation and protein ubiquitination, which were also associated with PD pathogenesis. Moreover, RT-qPCR assay verified the PCBP-1-modulated expression of neuroinflammatory genes, like LCN-2, and alternative splicing (AS) of ubiquitination-related gene WWP-2. Finally, CLIP-seq data analysis indicated that the first UC motif was the critical site for PCBP-1 binding to its targets. In this study, we provided evidence that PCBP-1 could regulate the expression of LCN-2 gene expression associated with neuroinflammation and AS of WWP-2 in relation to protein ubiquitination. These findings thus provided novel insights into the potential application of PCBP-1 as the disease pathophysiological or therapeutic target for neurodegenerative disease.